ChemInform Abstract: Ph‐tetraMe‐Bithienine, the First Member of the Class of Chiral Heterophosphepines: Synthesis, Electronic and Steric Properties, Metal Complexes and Catalytic Activity. Issue 21 (27th May 2014) - Vaghi, Luca; Benincori, Tiziana; Cirilli, Roberto; Alberico, Elisabetta; Mussini, Patrizia Romana; Pierini, Marco; Pilati, Tullio; Rizzo, Simona; Sannicolo, Francesco
Abstract The title ligand is synthesized and its utility for Rh‐catalyzed asymmetric hydrogenations as well as for the alkoxycyclization of enyne (V) is demonstrated.